State, science and empire in the portuguese atlantic (1770s–1820s) - Carolino, Luís Miguel (Portuguese Journal of Social Science, 2017)
This article argues that the strengthening of an Atlantic-based economy was the driving force of scientific development in the Portuguese empire during the late eighteenth and early nineteenth centuries. As a response to the structural crisis that distressed the Portuguese empire in the second half of the eighteenth century, a network of military institutions of higher technical and scientific education was established, first in Lisbon and later in Rio de Janeiro. State initiative was thus crucial in the modernizing process of the Luso-Brazilian empire. This produced profound consequences in the shaping of its scientific and technical framework. In particular, it resulted in the militarization of ‘Portuguese’ science, in the promotion of an applied science and in the social impact of a conception of the concept of the scientist as a military and practical man.